Connecting X-ray absorption and 21 cm neutral hydrogen absorption in obscured radio AGN - Moss, VA; Allison, JR; Sadler, EM; Urquhart, R; Soria, R; Callingham, JR; Curran, SJ; Musaeva, A; Mahony, EK; Glowacki, M; Farrell, SA; Bannister, KW; et al. (Oxford University Press, 2017)
Many radio galaxies show the presence of dense and dusty gas near the active nucleus. This can be traced by both 21 cm H I absorption and soft X-ray absorption, offering new insight into the physical nature of the circumnuclear medium of these distant galaxies. To better understand this relationship, we investigate soft X-ray absorption as an indicator for the detection of associated H I absorption, as part of preparation for the First Large Absorption Survey in H I to be undertaken with the Australian Square Kilometre Array Pathfinder (ASKAP). We present the results of our pilot study using the Boolardy Engineering Test Array, a precursor to ASKAP, to search for new absorption detections in radio sources brighter than 1 Jy that also feature soft X-ray absorption. Based on this pilot survey, we detected H I absorption towards the radio source PKS 1657−298 at a redshift of z = 0.42. This source also features the highest X-ray absorption ratio of our pilot sample by a factor of 3, which is consistent with our general findings that X-ray absorption predicates the presence of dense neutral gas. By comparing the X-ray properties of active galactic nuclei with and without detection of H I absorption at radio wavelengths, we find that X-ray hardness ratio and H I absorption optical depth are correlated at a statistical significance of 4.71σ. We conclude by considering the impact of these findings on future radio and X-ray absorption studies.